Towards a Critical Feminist Practice with Children and Families: Child Sexual Exploitation as an Exemplar. Issue 2 (15th March 2017) - Cooney, Lisa; Rogowski, Steve
Abstract : This article argues for a critical feminist practice in relation to social work with children and families, this being urgently required to provide help and support to such service users in male-privileged, neoliberal and managerialist times. Such practice is especially pertinent as far as teenage girls and their families are concerned. As an exemplar we focus on child sexual exploitation (CSE), and in turn adolescent girls in local authority care who are over-represented in cases of CSE. Through a critical feminist lens we also critique aspects of current policy and practice in relation to a phenomenon that has recently moved up the political and child protection agenda in the UK.